2015
DOI: 10.1017/s1431927615015007
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Guided Atomic Force Microscopy for Mechano-Visual Phenotyping of Cancer Specimens

Abstract: Atomic force microscopy (AFM) and other forms of scanning probe microscopy have been successfully used to assess biomechanical and bioelectrical characteristics of individual cells. When extending such approaches to heterogeneous tissue, there exists the added challenge of traversing the tissue while directing the probe to the exact location of the targeted biological components under study. Such maneuvers are extremely challenging owing to the relatively small field of view, limited availability of reliable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Tissue microarray specimens were imaged using Trestle® whole slide imaging system under a 20x objective. Custom whole slide visualization software [ 69 ] developed at Center for Biomedical Imaging & Informatics, Rutgers Cancer Institute of Pathology, was used to display high-resolution, synchronized, side-by-side views of corresponding TMA cores stained with RUNX2 and AXL and a board-certified pathologist examined tissue composition and staining intensity at each TMA core location. Quantification of RUNX2 expression was previously reported [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tissue microarray specimens were imaged using Trestle® whole slide imaging system under a 20x objective. Custom whole slide visualization software [ 69 ] developed at Center for Biomedical Imaging & Informatics, Rutgers Cancer Institute of Pathology, was used to display high-resolution, synchronized, side-by-side views of corresponding TMA cores stained with RUNX2 and AXL and a board-certified pathologist examined tissue composition and staining intensity at each TMA core location. Quantification of RUNX2 expression was previously reported [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several investigators have previously attempted to observe intracellular structures in tissue using AFM. However, suitable images were not acquired because these researchers used resin-embedded samples 6 12 . It is difficult to remove or dissolve the polymerized resin, even if the monomer is water-soluble.…”
Section: Discussionmentioning
confidence: 99%
“…A cryosectioning technique was applied to solve this problem. To observe fine structures in tissues with AFM, several previous studies have used conventional plastic sections 6 12 . However, only the cell contours and some organelles were faintly detected because the cutting surface of the resin-embedded sample was flat without removing the resin.…”
Section: Introductionmentioning
confidence: 99%
“…AFM has become a popular tool to study how the mechanical properties of tissues affect cancer development in laboratory settings [ 42 , 43 , 44 , 45 , 46 , 47 ]. It has been shown that cancer cells are highly deformable, allowing them to enter the bloodstream and spread to other organs, while tissues with cells that do not have such nanomechanical characteristics will not be able to metastasise [ 48 ].…”
Section: Development Of Fast It-afm For Clinical Tissue Diagnosismentioning
confidence: 99%